The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10334-004-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI study of PASAT in normal subjects

Abstract: The paced auditory serial addition test (PASAT) is routinely used to evaluate the cognitive part of the multiple sclerosis functional composite (MSFC) score, the new reference index of patient disability. PASAT is sensitive to subtle cognitive impairment related to MS, although the cognitive components of this test still remain unclear. In order to better characterize brain systems involved during this complex task, functional magnetic resonance imaging (fMRI) experiments were conducted during PASAT in a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 49 publications
9
56
0
Order By: Relevance
“…In line with the results of previous studies [9,10,12], when compared to HC, CIS patients showed an increased recruitment of several regions mainly located in the frontal and parietal lobes, bilaterally. All of these regions contribute to different aspects of working memory processing and the majority of them have been demonstrated to have a load-depending activity during working memory tasks [29,30].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with the results of previous studies [9,10,12], when compared to HC, CIS patients showed an increased recruitment of several regions mainly located in the frontal and parietal lobes, bilaterally. All of these regions contribute to different aspects of working memory processing and the majority of them have been demonstrated to have a load-depending activity during working memory tasks [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…They also had an increased connectivity between the R IFG and R IPL and between the L and R IPL compared to both CP patients and healthy controls, thus indicating an increased task demand for the R hemisphere in these patients. The notion that an increased recruitment of areas of the R hemisphere has a critical role for cognitive performance of MS patients agrees with previous activation [33,9,34] and connectivity [14] studies performed in patients with CIS and RRMS, as well as with several studies of the motor network (for a review, see Filippi and Rocca [36], which showed that a recruitment of homologous regions of the two hemispheres is one of the main compensatory mechanisms, at least at the earliest clinical phases of the disease. Differently from previous studies, which found abnormalities of brain recruitment in patients without overt clinical impairment [ 37, 38] our analysis did not reveal any abnormality of activation and connectivity between CP CIS patients and HC.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations